Lethal repetition: serial killing in European cinema - Dyer, Richard (BFI, 2015)
Cover -- Title -- Copyright -- Contents -- PREFACE -- ISSUES -- 1 THE PHANTOM MENACE -- 2 IS IT A SERIAL KILLER? -- 3 THE SAME OVER AND OVER -- 4 PROCURING EXTRAORDINARY SENSATIONS -- 5 MOTIVES LESS ADEQUATE -- 6 ACTION! KILL! CUT! -- CASES -- 7 SERIAL KILLING IN EUROPEAN CINEMA -- 8 'JACK THE RIPPER' -- 9 FROM HAARMANN TO HITLER TO HANNIBAL -- 10 ANYTHING, AND MORE, FOR THE FAMILY -- BIBLIOGRAPHY -- FILMOGRAPHY -- INDEX.